Plantations of Acacia auriculaeformis (Benth.) A. Cunn in West Bengal - Banerjee, A. K. (Indian Forester, 1973)
Acacia auriculaeformis, a native of Australia, has been tried in West Bengal in semi-arid sites, and has been found to be successful. The nursery soli-working, spacing. fertilisation techniques have been discussed. Also included in the paper are diameter, height, volume and yield of the species when raised in plantations in West Bengal.